Urinary tract infections in the Pediatric Unit of the Hospital Regional de Moquegua - Medina Valdivia, José Luis (2022)
Objective: To determine the clinical and epidemiological characteristics of urinary tract infections (UTIs) supported by the diagnosis, therapy and antimicrobial susceptibility of inpatients of the Pediatric Unit of the Hospital Regional de Moquegua from 2014 to 2020. Materials and methods: An observational, descriptive and retrospective study. The research included a population of 248 patients aged between 1 month and 14 years 11 months 30 days with a diagnosis of UTI who underwent a urine culture. A data collection sheet was used and the results were processed using the IBM SPSS Statistics statistical software 23.0. Results: The infection occurred more often in female patients (82.26 %), with fever being the most prevalent clinical manifestation (83.87 %). The most widely used medical treatment was amikacin (49.19 %). E. coli was the most frequently isolated germ (70.57 %). The isolated germs showed sensitivity to antibiotics such as nitrofurantoin (70.16 %), ceftazidime (51.20 %), gentamicin (43.14 %) and amikacin (28.62 %). In contrast, they were resistant to sulfamethoxazole–trimethoprim (74.59 %). One of the most common findings in the imaging tests was unilateral pyelectasis (43.14 %). Conclusions: UTIs occur more frequently in women. The anamnesis and clinical examination, together with a complete urinalysis and imaging tests, are essential for the diagnosis and treatment of these patients. The definitive diagnosis must be established by a urine culture. The choice of an empirical therapy will depend on the patient’s history of sensitivity and resistance to antibiotics based on the urine cultures performed.